Innovation Lab for Small Scale Irrigation (ILSSI) knowledge sharing workshop in Ethiopia - Bezabih, Melkamu (Texas A&M University, 2023)
On 25 May 2023, ILSSI organized a workshop in Addis Ababa, Ethiopia to share findings and lessons from the ten years of research for development work under the program. Attended by more than 80 participants from within and abroad, keynote speakers included ILRI’s Director General Representative to Ethiopia, State Minister for Irrigation and Lowlands, and representative to the USAID Ethiopia mission.